A Conflict Resolution Model Based on Local Wisdom And Prophetic Values : A Case Study Of The Integration of Religious Education in Cultural Mediation in Heterogeneous Schools - Nur Khikmah; Muhlisin; Muhammad Jaeni; Slamet Untung; Moh. Muslih (Lembaga Bale Literasi, 2025)
This research aims to design a conflict resolution model that integrates local wisdom and prophetic principles within heterogeneous educational contexts. Amidst the increasing threat of social disintegration in the world of education, Islamic Relegious Education serves a strategic role as an instrument for cultural mediation. Employing a qualitative approach through a case study at SMP Negeri 1 Pekalongan, this research investigates how prophetic valuses—such as Shiddiq, Amanah, Tabligh, and Fathanah—are integrated with local philosophies, such as Tepa Slira or Pela Gandong, to reduce identity-based tensions. The research finding indicate thaet this integrated model is proven effective in mitigating conflict through peer mediation strategies and the establishmen of superordinate goals.